Pathways and Water Mass Transformation Along and Across the Mohn‐Knipovich Ridge in the Nordic Seas - Ypma, Stefanie; Georgiou, S.; Dugstad, Johannes Sandanger; Pietrzak, J.D.; Katsman, C.A. (Journal of Geophysical Research: Oceans, 2020)
Atlantic Water takes various pathways through the Nordic Seas, and its transformation to denser waters forms a crucial connection to the lower limb of the Atlantic Meridional Overturning Circulation. Circulation maps often schematize two distinct pathways of Atlantic Water: one following the Norwegian Atlantic Slope Current along the continental slope of Norway and one following the Norwegian Atlantic Front Current along the Mohn and Knipovich Ridges. In this paper, the connectivity between the northward flow along these ridges is investigated. Analyzing trajectories of surface drifters and ARGO floats, we find that only 8% of the floats that travel near the mid-ocean ridges take the frontal pathway to the north. Indeed, by tracing numerical particles in a realistic numerical simulation, part of the water mass traveling along the Mohn Ridge follows the 2,500 m isobath eastward and joins the slope current, instead of flowing north along the Knipovich Ridge. Furthermore, north of 74°N, frequent exchange between the slope current and the front current is observed. Therefore, the slope current and front current are less isolated than often schematized. Additionally, the observational data set reveals substantial cross-ridge exchange; 31% of the floats that travel within 60 km from the mid-ocean ridges cross it. Results from numerical simulations indicate that the cross-ridge exchange leads to cooling and freshening of the Atlantic Water along the front. Deployments of floats near the mid-ocean ridges are needed to investigate the pathway of Atlantic Water and its exchange across the ridge in more detail. publishedVersion